2022
DOI: 10.1128/mra.00112-22
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequences of Mannanase-Producing Bacillus and Niallia Strains Isolated from the Intestine of the Black Tiger Shrimp (Penaeus monodon)

Abstract: Here, we report the complete genome sequences of mannanase-producing bacteria, namely, Niallia sp. strain Man26 and Bacillus subtilis strain Man122, isolated from the intestine of Penaeus monodon , the black tiger shrimp. Mannanases are used in various industries, such as food, animal feed, and biorefinery, to hydrolyze mannan to oligomers and mannose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…We previously determined complete full genome sequences of our bacterial candidates, Man26 and Man122, in which they showed similarity to Niallia sp. and Bacillus sp., respectively [ 43 ]. The morphological characteristics of the two isolates showed that both Man26 and Man122 were Gram positive with a rod shape ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…We previously determined complete full genome sequences of our bacterial candidates, Man26 and Man122, in which they showed similarity to Niallia sp. and Bacillus sp., respectively [ 43 ]. The morphological characteristics of the two isolates showed that both Man26 and Man122 were Gram positive with a rod shape ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%